AUTONOMOUS WEAPONS SYSTEM (AWS): WEAPON REVOLUTIONARY OR WEAPON OF MASS DESTRUCTION? - Riyanto, Sugeng; Iberahim, Muhammad M. (International Journal of Psychosocial Rehabilitation, 2020)
The autonomous weapons system (AWS) is a weapon that no longer involves human in its operation. It will move independently, look for its target, identify, and execute the target. This weapon is controlled by a robot equipped with artificial intelligence. This system is more advanced than drone technology (UCAV), which is still controlled by humans even from very distant range. Various parties claim that these weapons have more advantages compared to conventional weapons that are still controlled by humans. This weapon can eliminate mistakes that are often done by humans. The traits, quicker in scanning and making a decision, and free from situational human psychology (e.g., stress, et cetera.). This paper intends to explore the possible dangers posed by this weaponry system. This weapon system has a high priority on technological sophistication. Therefore, countries with advanced technology will be trapped in the increasingly extended lagging. This model weapon is also very likely to be produced by the private sector. Mass production carried out by the private sector will provide massive opportunities for the use of these weapons which are capable of mass destruction.